Self-healing supramolecular heterometallic gels based on the synergistic effect of the constituent metal ions. Issue 99 (26th October 2015) - Yan, Liwei; Shen, Linghong; Lv, Mingqian; Yu, Wenkun; Chen, Jie; Wang, Shuang; Fu, Xiaofang; Ye, Zhongbin
Abstract : Supramolecular heterometallic gels with synergistic properties were prepared for the first time using ligand1 with both Co 2+ and Ni 2+, and their macroscopic self-healing has been achieved by improving the unfavorable viscoelasticity of each monometallic gel. Abstract : Supramolecular heterometallic gels with synergistic properties were prepared for the first time using ligand1 with Co 2+ and Ni 2+, and their macroscopic self-healing has been achieved by improving the unfavorable viscoelasticity of each monometallic gel.